(Pengembangan Model Pembelajaran Motorik Dengan Modifikasi Permainan Tradisional Untuk Meningkatkan Motorik Kasar Anak Sekolah Dasar Kelas Bawah) - Hidayatullah, Muhammad Riyan; Hasbi, Hasbi (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to produce a motor learning model with modifications of traditional games for lower grade elementary school children. The stages of this research method are educational research and development (R & D) which adapts development research according to Borg & Gall (Kurdi & Sukadiyanto, 2014), namely: (1) potential and problems; (2) information collection; (3 ) product design (model draft); (4) expert validation and revision; (5) small-scale field trials and revisions; (6) large-scale field trials and revisions; (7) final product manufacture, revision of small-scale trials on 27 lower grade students namely grade II, and grade III at SDN 2 Gerung; (8) large-scale product trial on 40 grade II and third grade students at SD Negeri 1 Gerung; (9) product revision and, (10) benefits and implementation of the development of learning models.The instruments are: (1) interviews; (2) score scales; (3) teacher observations; (4) observation of the effectiveness of the model, and (5) student questionnaires. Data analysis techniques are descriptive qualitative and quantitative analysis. Results This research is in the form of a motor learning model with modifications a traditional game for lower grade elementary school children which contains five games, namely: (1) Gobak Sodor, (2) Jemprak/Engklek, (3) Grave Jumping, (4) Cat and Mouse, (5) Zig-Zag Sack Race, compiled in the form of a manual. From the results of data analysis on the assessment of material experts and student questionnaires, it can be concluded that the motor learning model with modified traditional games for lower grade elementary school children has a positive and effective response. This is evidenced by the percentage of each qualitative data requested is above 75% on a large scale, so that it can be used in physical education learning in elementary schools.